Analysis of the effect of high-frequency electromagnetic radiation on electroencephalography wave frequencies - Biševac, Boban; Lukić, Stevo; Stojković, Mina (Vojnosanitetski pregled, 2026)
Background/Aim. Interest in the effects of electromagnetic fields on the human organism has grown significantly with the advent of digital mobile communication systems, which employ pulsed high-frequency electromagnetic fields. In standby mode, a mobile phone does not emit significant signal power, while during active communication, the intensity of the electromagnetic field may reach values of up to 250 mW. The aim of this study was to examine whether exposure to high-frequency electromagnetic fields affects the frequency of electroencephalography (EEG) waves. Methods. The study included 60 participants (30 males and 30 females). Each participant underwent two consecutive EEG recordings, each lasting approximately 20 min. The first EEG recording was performed at rest, without exposure to an electromagnetic field generator. This was followed by a second EEG recording while using a mobile phone for 10 minutes on one ear, then a break of about 2 minutes was made and the recording was repeated on the opposite ear, also for 10 minutes. A standard mobile phone was used as the source of the high-frequency electromagnetic field. Results. The analysis of EEG wave frequencies revealed no statistically significant differences in either sex before and after mobile phone exposure in the alpha, beta, or delta frequency bands. A change in the theta frequency band in female participants following mobile phone exposure was localized to the right hemisphere. Conclusion. Methodological limitations are the most likely reason for the absence of recorded changes in the majority of participants. The observed effects may be sufficiently subtle or infrequent to evade detection by standard EEG recordings. Therefore, the lack of observed changes cannot be interpreted as evidence that high-frequency electromagnetic fields have no effect on EEG activity.
Keywords: cell phone; electroencephalography; electromagnetic fields; health; risk assessment